Simulasi Perpindahan Panas Pada Heater Injection Molding Menggunakan Software Solidworks - Munawar Alfansury Siregar; Riawansyah Riawansyah (Fakultas Teknik UMSU, 2018)
Plastic is a material that takes several years to decompose, so a recycling device such as an injection molding machine is needed. This injection molding is very good at managing useless plastic waste items that are worth the sale price. The purpose of this simulation analysis with solidworks software is to design the injection chamber and analyze it to get good results, so that there are no losses in making the engine later. Based on simulation data analysis is done by varying the heating temperature. Under heating conditions 150 ℃ the highest temperature distribution is 150 ℃ and the lowest is 146,196 ℃ with the lowest Heat flux 2,554,494 W / m ^ 2 and the highest Heat flux is 29,984.35 W / m ^ 2. Under heating conditions 200 ℃ the highest temperature distribution 150 ℃ and the lowest 194.611 ℃ with the lowest Heat flux 3,618,867 W / m ^ 2 and the highest Heat flux 42,477,828 W / m ^ 2. Under heating conditions 250 ℃ the highest temperature distribution of 150 ℃ and the lowest 243,027 ℃ with the lowest heat flux 4,683.24 W / m ^ 2 and the highest Heat flux 54,971,131 W / m ^ 2. From the analysis of injection chamber data the results are at a heating temperature of 150 ℃ producing a heat capacity of 41.99 KJ while at a heating temperature of 200 ℃ it produces a heat capacity of 59.49 KJ and at a heating temperature of 250 ℃ produces a heat capacity of 76.99 KJ.